Advances in Pathogenesis, Progression, Potential Targets and Targeted Therapeutic Strategies in SARS-CoV-2-Induced COVID-19 - Zhou, Hong; Ni, Wei-Jian; Huang, Wei; Wang, Zhen; Cai, Ming; Sun, Yan-Cai (Frontiers in Immunology, 2022)
As the new year of 2020 approaches, an acute respiratory disease quietly caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as coronavirus disease 2019 (COVID-19) was reported in Wuhan, China. Subsequently, COVID-19 broke out on a global scale and formed a global public health emergency. To date, the destruction that has lasted for more than two years has not stopped and has caused the virus to continuously evolve new mutant strains. SARS-CoV-2 infection has been shown to cause multiple complications and lead to severe disability and death, which has dealt a heavy blow to global development, not only in the medical field but also in social security, economic development, global cooperation and communication. To date, studies on the epidemiology, pathogenic mechanism and pathological characteristics of SARS-CoV-2-induced COVID-19, as well as target confirmation, drug screening, and clinical intervention have achieved remarkable effects. With the continuous efforts of the WHO, governments of various countries, and scientific research and medical personnel, the public's awareness of COVID-19 is gradually deepening, a variety of prevention methods and detection methods have been implemented, and multiple vaccines and drugs have been developed and urgently marketed. However, these do not appear to have completely stopped the pandemic and ravages of this virus. Meanwhile, research on SARS-CoV-2-induced COVID-19 has also seen some twists and controversies, such as potential drugs and the role of vaccines. In view of the fact that research on SARS-CoV-2 and COVID-19 has been extensive and in depth, this review will systematically update the current understanding of the epidemiology, transmission mechanism, pathological features, potential targets, promising drugs and ongoing clinical trials, which will provide important references and new directions for SARS-CoV-2 and COVID-19 research.